Research of The Rheological Properties of Melon as An Elastic Deforming Body - Saidhujaeva, Nafisa X (International Journal of Psychosocial Rehabilitation, 2020)
In article the elastic property of melon’s pulp is considered from the point of view of the physical laws of the mechanics. In a basis of judgements are applied the laws of Hook-Newton which are included in mathematical model by consideration of elastic - viscous properties of the Central Asian sorts of melon. The basis for the analytical description of model of a vegetative material on time, decompression of pressure(voltage) is incorporated by using mechanical processing of melon.